Integration of Cognitive-Behavioural Therapy with Adaptive Swimming Instruction for Children with Water-Related Anxiety Disorders: A Randomised Controlled Trial - Swandana, Atika; Ahmad , Nadhira Yasmine; Trinanda , Aditya; Al Azim, Al Azim; Porto , Jerome Angelitud (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2025)
The purpose of the study. To evaluate the effectiveness of an integrated swimming instruction program combining cognitive-behavioral therapy (CBT) principles with adaptive aquatic techniques for children with water-related anxiety disorders, comparing outcomes with traditional swimming instruction methods. Materials and methods. A randomized controlled trial involving 120 children aged 6-12 years with diagnosed anxiety disorders featuring water-related fears di kota Medan, Indonesia, Indonesia. Participants were assigned to either an intervention group (n=60) receiving specialized anxiety-focused instruction or a control group (n=60) receiving standard swimming lessons. The 12-week program included twice-weekly 45-minute sessions. Outcomes were measured using the Water Anxiety Scale for Children (WASC-R), Swimming Competency Assessment Tool (SCAT), Behavioral Observation Scale (BOS), and parent-reported anxiety measures (SCARED questionnaire). Results. The intervention group showed significantly greater improvements across all measures: anxiety reduction (68% vs 23% in controls), swimming competency (82% vs 45%), and avoidance behaviors (85% vs 35% reduction). Program completion rates were higher in the intervention group (95% vs 82%). At 3-month follow-up, the intervention group maintained superior outcomes in anxiety reduction (92% maintenance), swimming skills (88%), and water confidence (90%) compared to controls (76%, 70%, and 65% respectively). Conclusions. The integrated anxiety-focused swimming instruction approach significantly outperforms traditional methods for children with water-related anxiety disorders, producing superior outcomes in both psychological and physical domains while maintaining higher program adherence rates. This approach should be considered the standard of care for anxiety-affected populations in aquatic education.